Achieving Equity and Quality in Higher Education Global Perspectives in an Era of Widening Participation (Palgrave Studies in Excellence and Equity in Global Education, 2018)
Across the world, higher education is witnessing exponential growth in both student participation and types of educational providers. One key phenomenon of this growth is an increase in student diversity: governments are widening access to higher education for students from traditionally underrepresented groups. However, this raises questions about whether this rapid growth may in face compromise academic quality. This book presents case studies of how higher education institutions in diverse countries are maintaining academic excellence while increasing the access and participation of students from historically underrepresented backgrounds. Including case studies spanning four continents, the authors and editors examine whether increasing widening participation positively impacts upon academic quality. This volume will be of interest and value to students and scholars of global higher education, representation and participation in education, and quality in higher education.